The Struggle and Resistance against the limitations of women’s roles in Jane Austen’s Pride and Prejudice - Grace Reynaputri; Ruly Indra Dermawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study explores the struggle and resistance to the limitations imposed on women’s roles in Jane Austen’s Pride and Prejudice, with a specific focus on the character of Elizabeth Bennet. Set in a patriarchal society where social expectations and marriage norms largely shape women’s identities, the novel portrays Elizabeth as a woman who challenges traditional gender norms. This study uses feminist literary criticism and a qualitative descriptive methodology, specifically Simone de Beauvoir’s concept of The Other, to analyze how women are positioned as secondary subjects within a male-dominated social structure. The data were collected through close reading and textual analysis of narrative descriptions and dialogues related to women’s roles, marriage, and independence in the novel. The findings reveal that Elizabeth Bennet experiences various forms of social pressure to conform to traditional expectations, especially regarding marriage as an opportunity to secure a place in society and financial security. However, she resists these limitations by asserting her independence, valuing emotional integrity, and rejecting marriages that compromise her principles. Her critical attitude toward social hierarchy and her refusal of a financially secure yet loveless marriage show her resistance to patriarchal limitations. This study concludes that Elizabeth Bennet represents an early form of feminist awareness, representing the rights of women and self-expression in a socially restricted environment.